Sex‐specific foraging of an apex predator puts females at risk of human–wildlife conflict. Issue 7 (14th May 2021) - Schultz, Hendrik; Chang, Kevin; Bury, Sarah J.; Gaskett, Anne C.; Dennis, Todd E.; Ismar‐Rebitz, Stefanie M. H.; Southey, Ian; Hohnhold, Rebecca J.; Millar, Craig D.
Abstract: Urbanisation and anthropogenic alteration of ecosystems has led to conflict between humans and wildlife. Such conflict is often observed in apex predators. Although human–wildlife conflict has been extensively studied, male/female differences in behaviour are rarely considered. We investigated male/female differences in foraging behaviour of the predatory/scavenging brown skua Catharacta antarctica lonnbergi breeding on a New Zealand island nature reserve in proximity to farmland. These skuas are subject to culling, when perceived as a threat to livestock. As part of a long‐term ecological study, we used high‐resolution Global Positioning System (GPS) devices to characterise the space‐use of foraging brown skuas. We also analysed stable isotopes of carbon (δ 13 C) and nitrogen (δ 15 N) from modern and archived blood samples to investigate possible changes in diet over the past 30 years. Analysis of 100 GPS tracks collected from 2014 to 2016 demonstrated that males and females consistently visited different habitats. Males spent most of their time close to their breeding territory on the island nature reserve and females frequently visited a farmed island approximately two kilometres away. Consistent with this finding, we show that male and female skuas also differed markedly in their diets: males specialised on burrow‐nesting white‐faced storm petrels Pelagodroma marina (80%) with only a small proportion of sheep remains Ovis aries (<6%) contributing to their diet. In contrast, female diet comprised 27% white‐faced storm petrels, other seabirds (18%) and a relatively large proportion of sheep remains (47%). Further, our data (186 blood samples from 122 individuals) show that this male/female difference in diet has persisted at least since 1987. Because females fed disproportionally on sheep remains, they may be more vulnerable to being culled by farmers. Importantly, our case study suggests that intersexual differences in diet and foraging patterns can have major implications for the reproduction and survival of apex predators that interact with farming. We strongly suggest that intersexual differences in behaviour should be considered when investigating human–wildlife conflicts. Abstract : As the world's population grows, human activities increasingly overlap with wildlife. The authors show how intersexual differences put female brown skua at a heightened risk of culling. This study integrates tracking, with short‐ and long‐term stable isotope data and provides novel recommendations for resolving this and other human‐wildlife conflicts.